An Opportunity for Experiential Learning: Time for a reckoning in higher education - Park, Lark (Experiential Learning and Teaching in Higher Education, 2024)
The rise of artificial intelligence (generative and otherwise), the societal impacts of technology, as well as the coming economic disruptions to the labor market all point to an impending transformation for higher education. A rethinking and re-valuing of how, what, and where learning happens are due. Within this, an opportunity exists for experiential learning to move from periphery to the core in higher ed.